Contextual Geography Learning Based on Field Observation on the Physical Characteristics of the Alo Watershed - Hasan, Idris; Fitryane Lihawa; Nurfaika (International Journal of Technology and Education Research, 2026)
Geography learning demands an integration between conceptual understanding and empirical experience through direct observation of geospherical phenomena. However, geography learning is still often abstract and has not made optimal use of the surrounding environment as a source of contextual learning. This study aims to examine the geographical physical characteristics of the Alo Watershed (DAS) as a context of contextual geography learning based on field observation. This study uses a qualitative descriptive approach with a case study method carried out in the Alo watershed, Gorontalo Province. Data collection is carried out through field observation, documentation, and spatial data analysis which includes aspects of geomorphology, geology, hydrology, pedology, and biogeography. The results of the study show that the Alo watershed has an integrated geographical physical characteristics that are spatially arranged from upstream to downstream and can be observed directly in the field. These characteristics are not only available as physical phenomena, but also serve as sources and objects of geography learning that support contextual learning based on field observations. This study concludes that the Alo watershed has the potential to become an integrative and meaningful geography learning context and opens up opportunities for the development of local environment-based geography learning in a sustainable manner.